Optical Camera-Based Multiplexed Photonic Sensor System With Ultralow Detection Limit for Biomedical Applications - Pérez-Sánchez, Laura; Sánchez-Ramírez, Ana; Leuermann, Jonas; Molina-Fernández, Íñigo (IEEE, 2025)
Photonic sensors based on Mach–Zehnder interferometric architectures with phase-coherent readout have demonstrated their potential for the integration into medical diagnostic devices. Their compact design, low cost, and ability to detect multiple biomarkers make them potentially applicable for the point-of-care. Achieving both high throughput and optimal sensor performance requires a miniaturized interrogation system with multiplexed readout capability that facilitates alignment and at the same time offers a high signal-to-noise ratio (SNR). In this work, the use of an optical camera (OC)-based system suited for multiplexed integrated photonic sensor detection is investigated. Its system level model is derived to determine the SNR and its associated limit of detection (LOD). This model allows achieving optimal sensing performance by tuning the photonic chip, the optical system, and the camera detection parameters. In agreement with model expectations, experimental results show that this system allows reaching for bulk detection limits of ∼10−7 refractive index units (RIUs) for a system comprising three sensors, representing a state-of-the-art achievement.
Keywords: Fotónica; Interferómetros; Sensores; Señales, Teoría de (Telecomunicación); Biomedicina - Investigación; Limit of detection (LOD); Mach–Zehnder interferometer (MZI); Multiplexed sensor; Optical camera (OC); Signal-to-noise ratio (SNR)